The Rac1 Exchange Factor Dock5 Is Essential for Bone Resorption by Osteoclasts - Vives, Virginie (J Bone Miner Res, 2011)
Osteoporosis, which results from excessive bone resorption by osteoclasts, is the major cause of morbidity for elder people. Identification of clinically relevant regulators is needed to develop novel therapeutic strategies. Rho GTPases have essential functions in osteoclasts by regulating actin dynamics. This is of particular importance because actin cytoskeleton is essential to generate the sealing zone, an osteoclast-specific structure ultimately mediating bone resorption. Here we report that the atypical Rac1 exchange factor Dock5 is necessary for osteoclast function both in vitro and in vivo. We discovered that establishment of the sealing zone and consequently osteoclast resorbing activity in vitro require Dock5. Mechanistically, our results suggest that osteoclasts lacking Dock5 have impaired adhesion that can be explained by perturbed Rac1 and p130Cas activities. Consistent with these functional assays, we identified a novel small-molecule inhibitor of Dock5 capable of hindering osteoclast resorbing activity. To investigate the in vivo relevance of these findings, we studied Dock5(−/−) mice and found that they have increased trabecular bone mass with normal osteoclast numbers, confirming that Dock5 is essential for bone resorption but not for osteoclast differentiation. Taken together, our findings characterize Dock5 as a regulator of osteoclast function and as a potential novel target to develop antiosteoporotic treatments.